179 Dasotraline in Children With Attention Deficit Hyperactivity Disorder: Results of a Randomized, Double-Blind, Placebo-Controlled Study. (15th June 2018) - Goldman, Robert; Adler, Lenard; Spencer, Thomas; Findling, Robert; Hopkins, Seth C.; Koblan, Kenneth K.; Sarma, Kaushik; Hsu, Jay; Loebel, Antony
Abstract: Objectives: Once-daily dosing with dasotraline, a novel dopamine and norepinephrine reuptake inhibitor, achieves stable plasma concentrations over 24 hours with once-daily dosing. This study evaluated dasotraline in children aged 6–12 years (NCT02428088). Methods: Patients were randomized 1:1:1 to 6 weeks of once-daily, fixed-dose dasotraline 2 or 4 mg/day, or placebo. The primary efficacy endpoint was change from baseline (CFB) at Week 6 in ADHD Rating Scale Version IV – Home Version (ADHD RS-IV HV) total score, using a mixed model for repeated measures (MMRM) in the intent-to-treat (ITT) population. Secondary endpoints included Clinical Global Impression-Severity (CGI-S) score and safety endpoints. Results: The mean age of 342 randomized patients was 9.1 [SD: 1.9] years; 66.7% were male. Overall, 79% of patients completed the study. In the ITT population (N=336), ADHD RS-IV HV total score improved significantly with dasotraline 4 mg/day vs placebo(least squares [LS] mean [SE] CFB at Week 6: –17.53 [±1.31] vs –11.36 [±1.29], respectively, p<0.001; effect size [ES]: 0.48). Inattentiveness and hyperactivity/impulsivity subscale scores significantly improved with 4 mg/day vs placebo at Week 6 (p=0.001, p=0.003, respectively). Improvement in CGI-S score was statistically significant with dasotraline 4 mg/day vs placebo(LS mean [SE] CFB at Week 6: –1.39 [±0.12] vs –1.04 [±0.12], respectively, p=0.040; ES: 0.29). No significant improvement was observed on the ADHD RS-IV HV total score and the CGI-S score for dasotraline 2 mg/day vs placebo. The most frequent treatment-emergent AEs (≥5% and higher than placebo) were (2 mg/day; 4 mg/day; placebo): insomnia (15.3%; 21.7%; 4.3%, all terms combined), decreased appetite (12.6%; 21.7%; 5.2%), weight loss (5.4%; 8.7%; 0%), irritability (3.6%; 7.0%; 6.0%), nasopharyngitis (0.9%; 5.2%; 0.9%), and nausea (0%; 5.2%; 2.6%). Conclusions: Compared with placebo, dasotraline 4 mg/day significantly improved ADHD symptoms in children, as assessed by ADHD RS-IV HV total score and inattentiveness and hyperactivity/impulsivity subscale scores. Dasotraline was generally well tolerated; most common AEs were insomnia, decreased appetite, weight loss and irritability. Funding Acknowledgements: Study sponsored by Sunovion Pharmaceuticals Inc.